Pengaruh Teknik Pembelajaran Ice Breaking Terhadap Motivasi Ekstrinsik Belajar Siswa Pada Mata Pelajaran IPA - Bahri, Samsul; Dendi Tri Suarno (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2026)
Ice breaking is one of the learning techniques that is fun, creative, innovative, interesting in applying to the learning process. Based on the results of the researchers found problems, namely the lack of learning motivation, especially extrinsic motivation and students experiencing problems in learning concentration in science learning. Therefore, the purpose of the research is to find out how much influence the ice breaking learning technique has on the extrinsic motivation of students learning in science subjects in class III SD Negeri 06 Merau. The study used a quantitative approach of pre-experimental type one group pre-test post-test design. The sample amounted to 20 third grade students of SDN 06 Merau. Data collection techniques using questionnaires, interviews, and documentation. Data analysis used normality test and t-test. The results showed extrinsic motivation of students in learning science with a pre-test of 39% and a post-test of 60%. The results of hypothesis testing obtained t count 1.837 and t table 1.761. It can be concluded that Ha is accepted and Ho is rejected, ice breaking learning techniques have a significant effect on extrinsic motivation to learn science for third grade students of SDN 06 Merau.